The connective tissue and ligaments of the distal interphalangeal joint: a review and investigation using ultra-high field 16.4 Tesla magnetic resonance imaging. (May 2014) - Slattery, D.; Aland, C.; Durbridge, G.; Cowin, G.
This study reviews the literature on the anatomy of the connective tissues surrounding the distal interphalangeal joint and further characterizes the three-dimensional relationships of these structures with ultra-high field magnetic resonance imaging. Ten cadaver fingers, fixed in a solution of 5% agar and 4% formalin, were imaged utilising an ultrashield 16.4 Tesla ultra-high field magnetic resonance imaging, yielding a total of 4000 images. Images were analysed using Osirix™ (version 5.5.1 32 bit edition) for three-dimensional reconstruction. We found numerous conflicting descriptions of the connective tissue structures around the distal interphalangeal joint. Based upon our literature review and imaging studies we have defined precisely Cleland's ligaments, the oblique proximal septum, Grayson's ligaments, the dorsal plate, and the interosseous ligaments of the distal interphalangeal joint.